Hypotensive and Angiotensin-Converting Enzyme Inhibitory Activities of Eisenia fetida Extract in Spontaneously Hypertensive Rats. (22nd December 2015) - Mao, Shumei; Li, Chengde
Abstract : Objectives . This study aimed to investigate the antihypertensive effects of an Eisenia fetida extract (EFE) and its possible mechanisms in spontaneously hypertensive rats (SHR rats). Methods . Sixteen-week-old SHR rats and Wistar-Kyoto rats (WKY rats) were used in this study. Rats were, respectively, given EFE (EFE group), captopril (captopril group), or phosphate-buffered saline (PBS) (normal control group and SHR group) for 4 weeks. ACE inhibitory activity of EFE in vitro was determined. The systolic blood pressure (SBP) and diastolic blood pressure (DBP) were measured using a Rat Tail-Cuff Blood Pressure System. Levels of angiotensin II (Ang II), aldosterone (Ald), and 6-keto-prostaglandin F1 alpha (6-keto-PGF1 α ) in plasma were determined by radioimmunoassay, and serum nitric oxide (NO) concentration was measured by Griess reagent systems. Results . EFE had marked ACE inhibitory activity in vitro (IC50 = 2.5 mg/mL). After the 4-week drug management, SHR rats in EFE group and in captopril group had lower SBP and DBP, lower levels of Ang II and Ald, and higher levels of 6-keto-PGF1 α and NO than the SHR rats in SHR group. Conclusion . These results indicate that EFE has hypotensive effects in SHR rats and its effects might be associated with its ACE inhibitory activity.